2017
DOI: 10.1186/s40795-017-0174-y
|View full text |Cite
|
Sign up to set email alerts
|

Intention, magnitude and factors associated with bottle feeding among mothers of 0–23 months old children in Holeta town, Central Ethiopia: a cross sectional study

Abstract: Background: World Health Organization (WHO) recommends that bottle feeding should be avoided for infant and young child feeding since it has an impact on optimal breastfeeding, appropriate complementary feeding and bottles with a nipple are prone to contamination. The objectives of this study were to determine intention, magnitude and factors associated with bottle feeding among mothers of 0-23 months infants and children. Methods: Community based cross sectional study was conducted from February to May 2016. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 18 publications
4
27
5
Order By: Relevance
“…This misconception is further enhanced by the aggressive advertisement by artificial feeding companies. This finding is contrary to the findings of other studies where no significant relationship was found between infants’ gender and bottle feeding [14], or breastfeeding [15]. This was also contrary to another study where exclusive breastfeeding was significantly higher among male infants [17].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This misconception is further enhanced by the aggressive advertisement by artificial feeding companies. This finding is contrary to the findings of other studies where no significant relationship was found between infants’ gender and bottle feeding [14], or breastfeeding [15]. This was also contrary to another study where exclusive breastfeeding was significantly higher among male infants [17].…”
Section: Discussioncontrasting
confidence: 99%
“…The age of infants in the present study was shown to affect mothers’ choices of the method of feeding; where a higher percentage of the younger age group (< 6 months) were fed by breastfeeding in addition to formula compared to the older age groups who were fed artificial formula only. Similarly, young infants’ age (< 6 months) was associated with a higher prevalence of breastfeeding in a study performed in Ethiopia [14]. Our findings are consistent with the Egyptian DHS 2014 which stated that only 4 in 10 children under 6 months of age are being exclusively breastfed, and around 3 in 10 of children under 6 months are being bottle fed [5].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…It suggests that without any obvious problem of sucking and swallowing bottle feeding was started in full term children. 25.6% had H/O NICU stay for more than 24 hours. So, issue of separation of mother from baby was there in 25.6% only rest 74.6% children were there with mother only after birth.…”
Section: Original Research Articlementioning
confidence: 99%
“…Mothers who did not receive breast feeding education sessions from healthcare personnel during pregnancy and/or after delivery had almost two times risk of bottle feeding compared to mothers who received breast feeding education [22]. Breast feeding education is efficient for promotion of exclusive breastfeeding & also helpful to avoid harmful bottle feeding practice [24,25].…”
Section: Original Research Articlementioning
confidence: 99%